IMPLEMENTASIPASAL 36 “UNDANG-UNDANG BAHASA” - E. Zaenal Arifin (Pujangga: Jurnal Bahasa dan Sastra, 2015)
The Article 36 of Language Act requires the use of Indonesian in geographic names, the names of buildings, streets, apartments or settlements, offices, trade centers, trademarks, business institutions, and organizations or Indonesian legal entities. In reality, the “mandate” of this Act is inconsistently appreciated. There are still geographic names, buildings, trademarks and others do not use Indonesian. In adition, the writing of those names is varied and many of them disobey the spelling systems and diction.